Exploring Wind Energy Utilization in Sustainable Rental Office Building Design in Makassar - Abdul, Wahid; Yusuf, Firdaus (Journal of Engineering and Vocational Education, 2026)
Purpose of the study: This study aims to explore the integration of wind energy through wind turbine technology in the design of sustainable rental office buildings in Makassar City.Methodology: A qualitative exploratory approach was employed, including literature review, precedent study, site analysis, and wind potential assessment. Data were analyzed descriptively to formulate design strategies integrating wind turbines into building architecture.Main Findings: Makassar has average wind speeds of 2.5–3 m/s, suitable for small-scale wind turbines. Optimal building orientation, massing, and turbine placement on rooftops or facades enhance wind capture. Wind energy contributes to reduced conventional electricity consumption and supports sustainable building design.Novelty/Originality of this study: This research advances knowledge by harmoniously integrating wind turbine technology into architectural design, not merely as a technical add-on. It addresses the gap in wind energy exploration within building design, specifically for Makassar’s coastal context, promoting renewable energy adoption in sustainable architecture.